Guidance and Counseling Method of Islam in Overcoming Juvenile Delinquency in Tompobalang Village, Somba Opu District, Gowa Regency. - Syamsidar, Syamsidar; Asriyanti, St. (Jurnal Mercusuar, 2020)
Adolescence is a period of self-discovery and growth. This period is important as it will determine the character of the child when they grow up. Misbehavior is common during adolescence as teenagers have a strong curiosity. However, if not supervised properly, it is possible for them to fall into conditions that can damage their personality and social life.